O princípio da vedação do retrocesso e algumas limitações ao poder de tributar - Okamoto, Priscilla (2012)
The purpose of this study is to explore the possibility to apply the principle of the retrocession prohibition to some constitutional rules that deal with limitations on the taxing power. In order to accomplish this, first, the principle of retrocession prohibition was explored. Second, the research studied concepts related to the non cumulativity of ICMS, IPI, PIS/Pasep and Cofins, the ability to pay principle, the selectivity of the ICMS and IPI, the tax exemption, the immunity and the suitable tax treatment for the cooperative act. Based on each limitation, this work evaluated if it is possible to use the principle of retrocession prohibition to prevent the repeal of legislation that gives efficacy to these constitutional restrictions. The results have presented evidences that it is appropriate to apply this principle in some situations